Groundwater level prediction using support vektor machines and autoregressive (AR) modelss - Üneş, Fatih; Demirci, Mustafa; Kaya, Yunus Ziya; Ispir, Eyup; Mamak, Mustafa (International Conference “Environmental Engineering”, 2017)
Water resources managers can benefit from accurate prediction of the availability of groundwater. Ground water is a major source of water in Turkey for irrigation, water supply and industrial uses. The ground water level fluctuations depend on several factors such as rainfall, temperature, pumping etc. In this study, Hatay Amik Plain, Kumlu region was evaluated using Autoregressive (AR) and Support Vektor Machines (SVMs) methods. The monthly groundwater level was used the previous years data belonging to the Kumlu region.
Keywords: groundwater level; prediction; Amik plain; Support Vektor Machines (SVMs)